Entrepreneurial Effectiveness Factors for Accounting Study Program Students at UNP Kediri at E-commerce and Accounting Information System - Saifudin, Muhammad Agus; Linawati, Linawati; Zaman, Badrus (Universitas Nusantara PGRI Kediri, 2023)
Research Objective: The aim of this study was to determine the Entrepreneurial Effectiveness Factors for Students of the Accounting Study Program at Nusantara PGRI Kediri University in E-Commerce and Accounting Information Systems. Research Method: This research is an associative quantitative type. The sampling technique is purposive sampling. Respondents were 60 students majoring in Accounting for the 2018-2020 school year, with the criteria of having taken the accounting information systems (AIS) course. Data collection was carried out by distributing questionnaires using valid and reliable Google forms. Data analysis techniques to test the hypothesis using the SPSS version 21 program. Research Finding: The results showed that the E-Commerce variable had no effect on entrepreneurial effectiveness and for the Accounting Information System (SIA) variable it had an effect on entrepreneurial effectiveness.